PENGARUH INDEKS MAQASID SYARIAH DAN MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN PADA PERBANKAN SYARIAH DI INDONESIA - Ulfa, Nur Eliza; Suazhari, Suazhari (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This research aims to evaluate the effect of the Maqasid Sharia Index (MSI) and intellectual capital (IC) on the financial performance of Islamic banking projected by ROA in BUS Indonesia within the 2016-2020 period. This research takes the sample by using purposive sampling that contains some characteristic and can represent the population as well used in this research. This research contains 12 BUS observations which were multiplied by a five-year period so that the final number of samples observed was 60. The data collected by literature study and documentation method which is carried out by collecting relevant data from various sources and tracing the related BUS annual reports according to the year period used. This research used multiple linear regression analysis and processes by SPSS 22. The results show that MSI and Intellectual capital simultaneously affects the ROA while partially MSI has a negative affect toward ROA but Intellectual Capital has no influence on the financial performance projected by ROA of BUS in Indonesia.